Large posterior mediastinal ganglioneuroma with intradural cervical spine extension: A rare case report and review of literature. (December 2022) - Dahal, Alok; Malla, Justin Jung; Neupane, Durga; Lageju, Nimesh; Jaiswal, Lokesh Shekher; Chaudhary, Sushant; Kandel, Ashim; Chhetri, Sunit; Pahari, Soumya
Abstract: Introduction: Ganglioneuroma (GN) is a rare benign tumor of ganglion cell origin and can occur anywhere along the sympathetic chain. These tumors can grow to a significant size without any symptoms unless they exert a mass effect on the region they grow and start showing symptoms. Spinal extensions are rare and they may produce neurological symptoms warranting further investigation. Case presentation: We described a case of posterior mediastinal ganglioneuroma in a 4-year-old boy with cervical extension who presented with quadriparesis. The radiological scan revealed large ganglioneuroma having an intradural extramedullary extension with a large posterior mediastinal component compressing and displacing the surrounding structures. He underwent consecutive surgeries for complete excision of the tumor following which he regained his power in his upper and lower limbs over the period of 2 months. Conclusion: Para spinal mass with consistent radiological features suggests ganglioneuroma but confirmation should be done with biopsy. Complete excision of the tumor is the treatment of choice with close follow-up for clinical improvement and recurrence. Highlights: Ganglioneuroma is a rare neurogenic tumor that arises from the neural crest cells of the sympathetic ganglia. A multidisciplinary team approach should be used to plan the tumor's complete excision. Resection of the tumor is curative since these tumors are seldom malignant and have a low recurrence rate.